2016
DOI: 10.1186/s13167-016-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of personal characteristics in individual oral care

Abstract: AbstractsBackgroundPreventing diseases of oral cavity, specifically periodontal diseases, is currently a high-priority issue. Despite the wide selection of individual oral care products and the abundance of information on individual oral care, the prevalence of tooth decay and inflammatory periodontal diseases remains high. Apart from knowledge of individual oral care, of great importance for patients is their capacity to develop strong motivation for full-scale hygienic procedures.ResultsPatients’ motivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 7 publications
(6 reference statements)
1
9
2
Order By: Relevance
“…Numerous investigations have demonstrated that mothers' dental anxiety is a risk factor for dental caries in their children [4][5][6]. Our study's results conflict with these, indicating no positive correlation between maternal dental anxiety and high caries level among schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Numerous investigations have demonstrated that mothers' dental anxiety is a risk factor for dental caries in their children [4][5][6]. Our study's results conflict with these, indicating no positive correlation between maternal dental anxiety and high caries level among schoolchildren.…”
Section: Discussioncontrasting
confidence: 99%
“…Caring for children's health is usually the task of mothers, and besides that, maternal factors can influence the oral health of children by sharing genetic and environmental factors in the course of daily activities. Therefore, maternal oral health knowledge, behaviour, and perception are significant for preventing dental diseases in children [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The novel PPPM concepts have been suggested by EPMA to benefit the impacts on the oral and dental health [9][10][11]. It is well known that obesity interferes with dental practice and contributes to the development of many diseases, particularly in the oral cavity [12,13].…”
Section: Overviewmentioning
confidence: 99%
“…Inadequately provided oral health services in populations are caused by multi-factorial de cits including but not limited to low socio-economic status of affected individuals (low educational level and income), lack of insurance in sub-populations, insu cient density of dedicated medical units [20,21]. Another important aspect is the "participatory" medicine based on the active participation of population in maintaining oral health: Healthcare will remain insu cient as long as the patient is not motivated and does not feel responsible for their oral health [17,22,23,24]. To this end, nearly half of chronically diseased people do not comply with adequate medical services suffering from severely progressing pathologies [25].…”
Section: Introductionmentioning
confidence: 99%